Different corticostriatal integration in spiny projection neurons from direct and indirect pathways - Flores-Barrera, Edén; Vizcarra-Chacón, Bianca J.; Tapia, Dagoberto; Bargas, Jose; Galarraga, Elvira (Frontiers in Systems Neuroscience, 2010)
The striatum is the principal input structure of the basal ganglia (BG). Major glutamatergic afferents to the striatum come from the cerebral cortex and make monosynaptic contacts with medium spiny projection neurons (MSNs) and interneurons. Despite differences in axonal projections, dopamine receptors expression and differences in excitability between MSNs from “direct” and “indirect” BG pathways, these neuronal classes have been thought as electrophysiologically very similar. Based on work with BAC transgenic mice, here it is shown that corticostriatal responses in D1- and D2-receptor expressing MSNs (D1- and D2-MSNs) are radically different so as to establish an electrophysiological footprint that readily differentiates between them. Experiments in BAC mice allowed us to predict, with high probability (P>0.9), in rats or non-BAC mice, whether a recorded neuron, from rat or mouse, was going to be substance P or enkephalin immunoreactive. Responses are more prolonged and evoke more action potentials in D1-MSNs, while they are briefer and exhibit intrinsic autoregenerative responses in D2-MSNs. A main cause for these differences was the interaction of intrinsic properties with the inhibitory contribution in each response Inhibition always depressed corticostriatal depolarization in D2-MSNs, while it helped in sustaining prolonged depolarizations in D1-MSNs, in spite of depressing early discharge. Corticostriatal responses changed dramatically after striatal DA-depletion in 6-hydroxy-dopamine (6-OHDA) lesioned animals: a response reduction was seen in SP+ MSNs whereas an enhanced response was seen in ENK+ MSNs. The end result was that differences in the responses were greatly diminished after DA depletion.